Keeping an eye on eye care: monitoring progress towards effective coverage. Issue 10 (October 2021) - Keel, Stuart; Müller, Andreas; Block, Sandra; Bourne, Rupert; Burton, Matthew J; Chatterji, Somnath; He, Mingguang; Lansingh, Van C; Mathenge, Wanjiku; Mariotti, Silvio; Muirhead, Debbie; Rabiu, M Mansur; et al.
Summary: The eye care sector is well positioned to contribute to the advancement of universal health coverage within countries. Given the large unmet need for care associated with cataract and refractive error, coupled with the fact that highly cost-effective interventions exist, we propose that effective cataract surgery coverage (eCSC) and effective refractive error coverage (eREC) serve as ideal indicators to track progress in the uptake and quality of eye care services at the global level, and to monitor progress towards universal health coverage in general. Global targets for 2030 for these two indicators were endorsed by WHO Member States at the 74th World Health Assembly in May, 2021. To develop consensus on the data requirements and methods of calculating eCSC and eREC, WHO convened a series of expert consultations to make recommendations for standardising the definitions and measurement approaches for eCSC and eREC and to identify areas in which future work is required.